INFLUENCE OF LOCAL VIBRATION ON WORKERS IN FOUNDRY SHOPS - A. M. Lazarenkov; S. A. Horeva (Литьë и металлургия, 2016)
Influence of local vibration on workers in foundry shops is considered (distribution of occupational diseases according to professions and indicators of professional incidence of workers).